2013
DOI: 10.4317/jced.51170
|View full text |Cite
|
Sign up to set email alerts
|

Smear layer removal in canals shaped with reciprocating rotary systems

Abstract: The aim was to assess the presence of smear layer after canal instrumentation with two reciprocating rotary systems and a continuous motion one. Thirty canals were shaped with Reciproc, WaveOne or Mtwo systems. Smear layer was assessed following a three value scale at coronal, middle and apical levels with a scanning electron microscopy. Reciproc scores: coronal third, 20% of the cases: 0, 60%: 1, 20%: 2; middle third, 10%: 0, 20%: 1, 70%:2; apical third: 2 in all cases. WaveOne scores: coronal third, 0 (40%),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 23 publications
2
14
0
3
Order By: Relevance
“…In the apical third of the canals, instrumentation with Mtwo resulted in significantly less smear layer formation compared to Twisted and ProTaper instruments (p<0.001) [Table/ Fig-2,6]. This result is consistent with previous reports that showed Mtwo to be superior in cleaning efficacy compared to ProTaper files [9,10,16].…”
Section: Discussionsupporting
confidence: 82%
“…In the apical third of the canals, instrumentation with Mtwo resulted in significantly less smear layer formation compared to Twisted and ProTaper instruments (p<0.001) [Table/ Fig-2,6]. This result is consistent with previous reports that showed Mtwo to be superior in cleaning efficacy compared to ProTaper files [9,10,16].…”
Section: Discussionsupporting
confidence: 82%
“…In the present study a significant reduction in Enterococcus faecalis was observed after instrumentation of the root canal systems of deciduous molars using the WaveOne system, in agreement with others authors who observed similar canal cleaning capacity when different rotary and reciprocating systems were compared (WaveOne, Reciproc and MTwo) [19]. The WaveOne and Reciproc system exhibited similar efficacy for cleaning root canals in a previous study [20].…”
Section: Discussionsupporting
confidence: 79%
“…For standardisation purpose, working lengths were established at À1 mm from the foramen in all samples; preparation and irrigation protocols were identical for both groups. It could be concluded that metallurgical properties and files design were more decisive than the number of instruments used and their kinematics on the cutting efficiency, debris production and thus the cleaning abilities of the files (12)(13)(14)(15). When comparing instruments in reciprocating motion of first generation WaveOne â and Reciproc â , similar effectiveness regarding the cleanliness of the apical third were found (9,10).…”
Section: Discussionmentioning
confidence: 88%